An organisational study into the impact of mobile devices on clinician and patient experience in Auckland, New Zealand - Kelly Bohot; Rebecca Hammond; Teresa Stanbrook (The Beryl Institute, 2017)
Mobile technology has potential to improve workflow, patient safety and quality of care, and has been identified as an important enabler of community services. However, little is known about the impact of mobile device use on clinician and patient experiences. Eleven community allied health clinicians were provided with live access to electronic health records, their email and electronic calendar, peer reviewed education and therapy mobile applications via a mobile device. Three data measures were collected over 19-weeks. First, quantitative time and motion data was gathered at baseline and follow-up to enable longitudinal analysis of clinician workflow. Second, a questionnaire consisting of rateable statements, multi-choice and open questions was completed at baseline and follow-up to enable analysis of clinician experience. Third, a short questionnaire was completed with a convenience sample of 101 patients who experienced mobile device use in their home. Clinicians and patients reported positive experiences associated with access to electronic health information at the point of care and the use of pictures, diagrams and videos to support clinical interactions. There was a significant reduction in time spent on patient related administration (p